МЕКТЕПТИ ЖӘМӘӘТЛИК БАСҚАРЫЎДА АТА-АНАЛАР МЕНЕН ИСЛЕСИЎДИҢ ӘҲМИЙЕТИ - Меңлибаева, А.О.; Омаров, С.С. (FAN va JAMIYAT, 2020)
Authors pay special attention on the principles and peculiarities of school management. Methodical and theoretical recommendations are present to teacher on how to work with parents in school management. Investistigating this problem is very significant in our Republic.